2014
DOI: 10.1093/jac/dku386
|View full text |Cite
|
Sign up to set email alerts
|

Ceftobiprole and ampicillin increase daptomycin susceptibility of daptomycin-susceptible and -resistant VRE

Abstract: Ceftobiprole appears to offer a similar degree of synergistic activity to ampicillin when combined with daptomycin against VRE. Further research should explore the genetic and phenotypic qualities of strains that respond preferentially to ceftobiprole as opposed to ampicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The beta-lactam concentrations used in the combinations were 0.5 ϫ the MICs listed below or the biological free peak concentrations presented in the text, whichever one was lower. (A) Strain 8019; ORI MIC, 0.125 g/ml; AMP MIC, Ͼ128 g/ml; ERT MIC, Ͼ32 g/ml; CPT MIC, 32 g/ml; (B) strain R6815; ORI MIC, 0.125 g/ml; AMP MIC, Ͼ64 g/ml; ERT MIC, Ͼ32 g/ml; CPT MIC, Ͼ64 g/ml; (C) strain R7164; ORI MIC, 0.125 g/ml; AMP MIC, 8 g/ml; ERT MIC, Ͼ32 g/ml; CPT MIC, been demonstrated when beta-lactams were combined with VAN or DAP, and the findings of our study suggest that beta-lactams confer similar benefits upon ORI in vitro (22,23,(25)(26)(27)(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The beta-lactam concentrations used in the combinations were 0.5 ϫ the MICs listed below or the biological free peak concentrations presented in the text, whichever one was lower. (A) Strain 8019; ORI MIC, 0.125 g/ml; AMP MIC, Ͼ128 g/ml; ERT MIC, Ͼ32 g/ml; CPT MIC, 32 g/ml; (B) strain R6815; ORI MIC, 0.125 g/ml; AMP MIC, Ͼ64 g/ml; ERT MIC, Ͼ32 g/ml; CPT MIC, Ͼ64 g/ml; (C) strain R7164; ORI MIC, 0.125 g/ml; AMP MIC, 8 g/ml; ERT MIC, Ͼ32 g/ml; CPT MIC, been demonstrated when beta-lactams were combined with VAN or DAP, and the findings of our study suggest that beta-lactams confer similar benefits upon ORI in vitro (22,23,(25)(26)(27)(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 64%
“…In vitro time-kill experiments have demonstrated the concentration-dependent bactericidal activity of ORI against daptomycin-nonsusceptible (DNS) MRSA, VAN-intermediate S. aureus (VISA), heteroresistant VISA (hVISA), and VRE in 24-h time-kill experiments (17)(18)(19)(20). Recent data suggest that lipopeptides and glycopeptides demonstrate enhanced activity against these resistant, Gram-positive organisms when beta-lactams are added (9,13,15,16,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). However, the activity of ORI in combination with beta-lactams against multidrug-resistant MRSA or VRE strains has yet to be evaluated.…”
mentioning
confidence: 99%
“…CRO and AMP together are active against PBPs 1 to 5, and recent clinical data describing the effective use of this combination further establish this possibility (43). Recent data have also demonstrated that ceftobiprole is synergistic with DAP against VRE that are both DAP susceptible and DAP nonsusceptible (44). Previous work has demonstrated that ceftobiprole possesses activity against enterococcal PBP5 and PBPs 1 to 4 similar to, although not quite as potent as, that of CPT (40).…”
Section: Discussionmentioning
confidence: 89%
“…This is an intriguing possibility to be further investigated in clinical studies, since it could represent an important option for salvage therapy of MRSA bacteremia and/or endocarditis. Of note, synergy between ceftobiprole and daptomycin has also been demonstrated against enterococci, including vancomycin-resistant isolates [20,53]. However, the related evidence is currently limited to in vitro studies, and further evidence from either animal models or clinical studies is needed regarding the possible use of ceftobiprole/daptomycin combinations for severe enterococcal infections in humans.…”
Section: Bacteremia Endocarditis and Mediastinitismentioning
confidence: 99%